PERAN PENTING LINGKUNGAN SEKOLAH DAN DUKUNGAN ORANG TUA DALAM MELANJUTKAN PENDIDIKAN - Amelia, Yessica; Rizal, Muhammad; Austin, Diani (INOPENDAS: Jurnal Ilmiah Kependidikan, 2024)
Continuing education is essential in today's rapidly evolving world, allowing individuals to adapt to new challenges, broaden their horizons, and improve their skills. This research aims to explore the significant impact of the school environment and parental support on students' interest in continuing their education. Researchers used descriptive quantitative methods with cluster sampling techniques for 219 respondents. The results of this study explain a significant effect. A school environment that provides access to various learning opportunities can inspire enthusiasm for continuous learning and empower students to achieve educational goals. Additionally, parental support is critical in ensuring successful continuing education. Parents can instill a strong work ethic, resilience, and growth mindset for lifelong learning by encouraging their children to set goals, providing guidance, and offering emotional support.